More than a market. How German companies are growing roots in Chinese society (Gütersloh, 2016)
"This publication is intended as an "idea book" for anyone concerned with the question of how German companies can establish and grow roots in Chinese society. It explores what is happening at the intersection of German companies, the Chinese market and Chinese society."